Pengembangan LKPD Berbasis Model Group to Group Exchange (GGE) Pada Materi Koloid - Fitraliana, Fitraliana; Hanum, Latifah; Rahmayani, Ratu Fazlia Inda (Jurnal Ilmiah Mahasiswa Pendidikan Kimia, 2024)
The research has been carried out on the development of LKPD based on the GGE model on colloidal material at SMAN 4, SMAN 8, SMAN 11, and SMAN 12 Banda Aceh. The objectives of this study are to: (1) analyze the feasibility of the LKPD based on the GGE model that has been developed on colloidal material, (2) describe the responses of class XI chemistry teachers at SMA Banda Aceh to the LKPD based on the GGE model. This study uses a qualitative approach that produces descriptive data. The type of research used is Research and Development (RD) with a 4-D model with four stages, namely (1) Define, (2) Design, (3) Develop and (4) Disseminate. The sampling technique was carried out by purposive sampling. The study was conducted in four schools, namely SMAN 4, SMAN 8, SMAN 11 and SMAN 12 Banda Aceh. This study obtained results, namely (1) the validation of the feasibility of the LKPD by expert validators by 90% and based on the assessment of chemistry teachers by 89% in the very feasible category and (2) the results of the chemistry teachers' responses to the LKPD by 99% in the very category. good. Based on the results of the study, it can be concluded that the LKPD based on the GGE model on colloidal material is valid and feasible to be used as teaching material on colloidal material.Keywords: Development, LKPD, GGE, Colloid